2020
DOI: 10.1016/j.jagp.2020.08.007
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, Psychological Well-being and Physical Activity Levels in Older Adults During the Nationwide Lockdown in Spain

Abstract: Highlights We aimed to assess the mental status of older adults during the COVID-19 epidemic, exploring whether meeting the World Health Organization global recommendations on physical activity for health was associated with it. Our results showed that older adults who meet the global recommendations on vigorous and moderate-vigorous physical activity had higher resilience, positive affect, and lower depressive symptoms. This is the first quantitative veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
213
0
19

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(249 citation statements)
references
References 44 publications
17
213
0
19
Order By: Relevance
“…Particular attention should be given to the psychological domain, which seems to indicate a relapse to depressive nuances related to the loss of pleasure for one’s life. Furthermore, it might be that the shelter-in-place order could have led to restrictions in physical activity behavior [ 6 ], with a possible significant negative impact on psychological well-being and QoL. In fact, recent literature suggests that daily physical activity helped to offset the psychological burden and negative emotions caused by COVID-19 pandemic [ 6 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Particular attention should be given to the psychological domain, which seems to indicate a relapse to depressive nuances related to the loss of pleasure for one’s life. Furthermore, it might be that the shelter-in-place order could have led to restrictions in physical activity behavior [ 6 ], with a possible significant negative impact on psychological well-being and QoL. In fact, recent literature suggests that daily physical activity helped to offset the psychological burden and negative emotions caused by COVID-19 pandemic [ 6 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it might be that the shelter-in-place order could have led to restrictions in physical activity behavior [ 6 ], with a possible significant negative impact on psychological well-being and QoL. In fact, recent literature suggests that daily physical activity helped to offset the psychological burden and negative emotions caused by COVID-19 pandemic [ 6 , 7 , 8 ]. A possible explanation is that regular exercise is linked to change in hypothalamic–pituitary–adrenal (HPA) axis, with reduced adrenal, autonomic, and psychological responses to a psychosocial stressor [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous Spanish surveys during the lockdown, older persons showed less emotional distress and higher resilience to the pandemic than younger adults [ 43 ]. However, the profile of resilient individuals seemed to be characterized by more optimistic personality traits [ 44 ], a regular practice of vigorous and moderate PA, positive self-perceptions of ageing, less depressive symptoms [ 45 , 46 ] as well as less perceived loneliness during the lockdown [ 47 ]. It is possible that, in these surveys, vulnerable responders were not sufficiently represented.…”
Section: Discussionmentioning
confidence: 99%
“…Once it was identified that the individual met the inclusion criteria and agreed to participate, his/her email address or, failing that, the email address of a close relative was requested to send the online survey. This type of survey has been used in other studies with old people during the pandemic of COVID-19 (Carriedo et al 2020 ). Online snowball sampling has been shown to be adequate to contact participants from different places and reaching higher response rates than other sampling strategies (Baltar and Brunet 2012 ).…”
Section: Methodsmentioning
confidence: 99%